ANALISIS KELAYAKAN MATERI TEKS ANEKDOT PADA BUKU BAHASA INDONESIA KELAS X - Rosmawaty; Theo Theoklistus Nong Abella; Nanda Yuliana Sinaga; Citra Patmasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the feasibility of anecdotal text material in Indonesian language textbooks for grade 10. The focus of the study is directed at the suitability of the content to the curriculum, language suitability, presentation techniques, and graphic aspects. The analysis was conducted by utilizing findings from various previous studies that highlight the quality of local wisdom-based teaching materials, the development of narrative modules, the use of digital media such as Powtoon, the use of image media, and syntactic evaluation in the Independent Curriculum. The results of the study indicate that the anecdotal text material in grade 10 textbooks generally meets the feasibility standards, both in terms of content and communicative language. However, limitations are still found in the variety of presentations, consistency of structure, and the use of supporting media relevant to the learning context. This study emphasizes the importance of developing teaching materials that are more contextual, innovative, and appropriate to the characteristics of students so that Indonesian language learning can take place more effectively. Thus, this study provides recommendations for teachers and textbook compilers to continuously update anecdotal text material according to curriculum demands and student needs.